Malaria parasite LIMP protein regulates sporozoite gliding motility and infectivity in mosquito and mammalian hosts - Santos, Jorge M.; Egarter, Saskia; Kumar, Hirdesh; Moreau, Catherine; Kehrer, Jessica; Frischknecht, Friedrich; Mair, Gunnar R. (eLife, 2017)
Gliding motility allows malaria parasites to migrate and invade tissues and cells in different hosts. It requires parasite surface proteins to provide attachment to host cells and extracellular matrices. Here, we identify the Plasmodium protein LIMP (the name refers to a gliding phenotype in the sporozoite arising from epitope tagging of the endogenous protein) as a key regulator for adhesion during gliding motility in the rodent malaria model P. berghei. Transcribed in gametocytes, LIMP is translated in the ookinete from maternal mRNA, and later in the sporozoite. The absence of LIMP reduces initial mosquito infection by 50%, impedes salivary gland invasion 10-fold, and causes a complete absence of liver invasion as mutants fail to attach to host cells. GFP tagging of LIMP caused a limping defect during movement with reduced speed and transient curvature changes of the parasite. LIMP is an essential motility and invasion factor necessary for malaria transmission.